Identifikasi dan Uji Kemampuan Hidrolisis pada Bakteri Amilolitik dan Proteolitik yang Diisolasi dari Wadi, Makanan Khas Kalimantan Tengah - Hesti Nur Choirunnisa; Ria Yustika Sari; Utami Sri Hastuti; Agung Witjoro (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2017)
Wadi is a sort of traditional foods that made of fish from Dayak tribe in Central Kalimantan. Wadi is made bythe addition of salt and lumu. People make wadi as a supply of side dishes during difficult seasons of fish andstock for farming, hunting, or collecting forest products. In wadi, there are several bacteria species that capablein degrading amylum and protein. The bacteria capability in amylum and protein degradation can be determinedby calculating the hydrolysis index. The aims of this study is to: (1) identify the amylolytic bacteria andproteolytic bacteria species from wadi, (2) determine the amylum and protein hydrolysis index on eachamylolytic bacteria and proteolytic bacteria species isolated from wadi, and (3) determine the amylolyticbacteria and proteolytic bacteria species that have the highest hydrolysis index. This research is descriptiveexplorative research. The research results showed that: (1) there were four isolates of amylolytic bacteriaisolated from wadi, i.e: Enterobacter agglomerans, Pseudomonas fluorescens, Acinetobacter baumannii, andMicrococcus varians, and there were five species of isolated proteolytic bacteria from wadi, i.e: Enterobacteragglomerans, Pseudomonas fluorescens, Nitrococcus mobilis, Acinetobacter baumannii, and Micrococcusvarians, (2) the amylum hydrolysis index of Enterobacter agglomerans is 3.77; on Pseudomonas fluorescensis 3.00; on Acinetobacter baumannii is 4.16; and on Micrococcus varians is 7.23. The protein hydrolysis indexof Enterobacter agglomerans is 3.22; on Pseudomonas fluorescens is 2.25; on Nitrococcus mobilis is 1.67; onAcinetobacter baumannii is 3.42; and on Micrococcus varians is 3.45, (3) Micrococcus varians has the highestamylum, i.e: 7.23 and protein hydrolysis index is 3.45.